1995
DOI: 10.1007/bf00240963
|View full text |Cite
|
Sign up to set email alerts
|

Focal depression of cortical excitability induced by fatiguing muscle contraction: a transcranial magnetic stimulation study

Abstract: Motor evoked potentials (MEPs) elicited by transcranial magnetic stimulation (TMS) and transcranial electrical stimulation (TES) of the motor cortex were recorded in separate sessions to assess changes in motor cortex excitability after a fatiguing isometric maximal voluntary contraction (MVC) of the right ankle dorsal flexor muscles. Five healthy male subjects, aged 37.4 +/- 4.2 years (mean +/- SE), were seated in a chair equipped with a load cell to measure dorsiflexion force. TMS or TES was delivered over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
79
1

Year Published

1997
1997
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 26 publications
15
79
1
Order By: Relevance
“…The changes in motor cortical excitability described in this study are central in origin as FDI potentials evoked by electrical stimulation of the ulnar nerve were not modi®ed during the exercise and rest periods. In other experiments on the effects of exercise on motor cortical excitability, the role of spinal or peripheral nerve changes have been excluded (Brasil-Neto et al, 1993;McKay et al, 1995;Zanette et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The changes in motor cortical excitability described in this study are central in origin as FDI potentials evoked by electrical stimulation of the ulnar nerve were not modi®ed during the exercise and rest periods. In other experiments on the effects of exercise on motor cortical excitability, the role of spinal or peripheral nerve changes have been excluded (Brasil-Neto et al, 1993;McKay et al, 1995;Zanette et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Motor cortex excitability is affected immediately before movement onset (Starr et al, 1988;Reynolds and Ashby, 1999), continues during the course of movement (Ljubisavljevic et al, 1996;Sacco et al, 1997;Aranyi et al, 1998;Tinazzi and Zanette, 1998), and may even persist following movement (Brasil-Neto et al, 1993McKay et al, 1995;Zanette et al, 1995;Bonato et al, 1996;Liepert et al, 1996;Samii et al, 1996Samii et al, , 1997. If movements are continued until`exhaustion' (de®ned by an inability to maintain at least 50% of maximal force), MEPs are reduced for up to 15 min, a phenomenon termed post-exercise depression (Brasil-Neto et al, 1993McKay et al, 1995;Liepert et al, 1996;Samii et al, 1996Samii et al, , 1997.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study showed that post-exercise MEP responses to TMS had decreased in amplitude relative to pre-exercise responses (post-exercise MEP depression). A follow-up study by Brasil-Neto et al (1994) and studies from other groups (McKay et al 1995;Liepert et al 1996;Samii et al 1996a,b) showed that the post-exercise MEP depression is often preceded by an initial short-duration increase in the post-exercise MEP amplitudes relative to pre-exercise responses (post-exercise MEP facilitation). Brasil-Neto et al (1994) demonstrated that MEP amplitudes were reduced to less than half pre-exercise values after an exercise protocol.…”
mentioning
confidence: 97%
“…Samii et al (1996a,b) and Liepert et al (1996) studied the post-exercise changes in the arm and in the small muscles of the hand. McKay et al (1995) were the first group to look at the effects of exercise on TMS-induced responses in the lower limb. Whether or not lower and upper limb muscles respond to exercise in the same manner is still under debate.…”
mentioning
confidence: 99%